Analysis on heat transfer performance of coaxial borehole heat exchanger in a layered subsurface with groundwater - Xiaoliang He; Jie Li; Yiqi Chen; Baojun Niu (Heliyon, 2024)
In the realm of ground source heat pump (GSHP) installations, the operational efficiency of borehole heat exchangers (BHEs) is heavily dependent on the complex configurations of geological formations, including soil stratification and the movement of underground water. Our research investigated the influences of ground structure characteristics on the heat transfer performance of coaxial BHEs. A coaxial borehole heat exchanger with a three-dimensional design was constructed, setting a typical geology from the Xiong'an New Region as the boundary condition. The homogenous model with equivalent physical properties overpredicted the water temperature exiting the coaxial BHE in the stratified ground with groundwater advection by 0.2 °C, while underpredicted the heat transfer rate by 10.8 % for the 24-h period; There exists an optimal inlet flow velocity to balance the heat injection and enhanced heat transfer for the optimal heat transfer rate, which was 0.4 m/s in this study; The increase of groundwater advection velocity decreased the outlet temperature by 0.5 %, enhanced the heat transfer per meter by 15.5 % and contributed to a smaller thermal influence radius during the 24-h period. This will contribute to the design of coaxial BHEs in complex geological structure.